The Nature of Differentiated Learning in The Perspective of Constructivist Educational Philosophy: A Systematic Literature Review - Umayrah, Anggi; Iswara, Prana Dwija; Salsabila, Syifa; Azzahra, Siti Silmi; Jeujanan, Mariana (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to examine differentiated learning from the perspective of constructivist educational philosophy, namely the application of differentiated learning and the relationship between constructivism and differentiated learning. This research used a qualitative approach, with a systematic literature review method using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis). This research used the Publish or Perish application to search for various relevant scientific articles taken from international journals, Scopus, with a range of 2014-2024. The data analysis technique for this research used thematic analysis. The result showed that the nature of learning differs from the perspective of constructivist educational philosophy regarding basically every student's knowledge. Constructivism includes a learning process where students must build their knowledge through knowledge and experience that has existed in students before. In learning, teachers help students reconstruct information by presenting meaningful learning. Meaningful in this sense, teachers must be able to organize learning by considering each student's uniqueness because each student is a different individual. The findings in this study showed that the application of differentiated learning based on the educational philosophy of constructivism can be a reference for teachers to direct students in constructing their knowledge independently by paying attention to all aspects of each student's learning. The implication of this study is to provide knowledge to teachers and prospective teachers, namely that the educational philosophy of constructivism can guide learning theory in the application of differentiated learning. Later, it can help improve the quality of learning, which will also increase human resources in Indonesia and help achieve national development goals.